(untitled) (TAMADDUN NURI JURNALI, 2025)
The article analyzes the names of water bodies used in K.Allambergenov’s novel "The years when the river frozen". In the Karakalpak language, hydronyms specific to the language of the local population, hydronym appeals specific to the national literary language, have been studied from a linguistic point of view.